2005
DOI: 10.1038/sj.bjc.6602564
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical relevance of dosing time for the therapeutic index of gemcitabine–cisplatin

Abstract: The relevance of gemcitabine timing for chronotherapeutic optimisation was investigated. Healthy mice received multiple doses of gemcitabine (120, 160 or 200 mg kg À1 injection (inj) À1 ) at one of six circadian times (3, 7, 11, 15, 19 or 23 h after light onset -HALO) on days 1, 4, 7 and 10 or a single dose of gemcitabine (400 mg kg À1 ) at 11 or 23 HALO7cisplatin (5 mg kg À1 at 1 min, 4 or 8 h later). Mice bearing Glasgow osteosarcoma received multiple doses of gemcitabine (200 mg kg À1 inj À1 ) at 11 or 23 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…[20][21][22][23] Anticancer drugs are also chronologically considered for scheduling to reduce side effects and enhance antitumor activity. [24][25][26][27][28] These results indicate that the susceptibility of tumor cells to anticancer agents oscillates. Moreover, the efficacy of antiangiogenic therapy depends on dosing time, 14,29) since the previous report suggested that VEGF production also fluctuates in a circadian fashion.…”
Section: Discussionmentioning
confidence: 94%
“…[20][21][22][23] Anticancer drugs are also chronologically considered for scheduling to reduce side effects and enhance antitumor activity. [24][25][26][27][28] These results indicate that the susceptibility of tumor cells to anticancer agents oscillates. Moreover, the efficacy of antiangiogenic therapy depends on dosing time, 14,29) since the previous report suggested that VEGF production also fluctuates in a circadian fashion.…”
Section: Discussionmentioning
confidence: 94%
“…Dedicated chronobiologic animal facilities allow setup light onset at the desired time for different groups of animals located on different isolated shelves, so that different circadian stages are tested at the most convenient times (46). Figure 3 depicts the times of least toxicity and benefit from optimal circadian timing, referring to external LD synchronizer and internal average body temperature rhythm for 16 anticancer drugs in male B6D2F1 mice (female C57BL/6 × male DBA2) in studies performed at our laboratory (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62)(63). The optimal circadian timings are staggered along the 24-h period and cannot be predicted thus far by the knowledge of pharmacologic class or that of main target organs for toxicity.…”
Section: The Relevance Of Circadian Timing For Treatment Tolerabilitymentioning
confidence: 99%
“…Circadian rhythms in the tolerability of anticancer drugs persist in rodents kept in constant darkness or in constant light, which demonstrates their endogenicity (64). Even when combined, chemotherapeutic agents display the least toxicity near their respective times of best tolerability as single agents, as shown for doxorubicin-cisplatin in Lou rats, irinotecanoxaliplatin or gemcitabine-cisplatin in B6D2F1 mice, and docetaxel-doxorubicin in C3H/He mice (56,(65)(66)(67). These findings support the persistence of the circadian control of anticancer drug determinants after exposure to the first anticancer agent, at least when the latter is given near the time of best tolerability.…”
Section: The Relevance Of Circadian Timing For Treatment Tolerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Therapy was repeated once every 7 days for a total of 4 injections. The dose of gemcitabine used was based on the reported [43][44][45] and confirmed LD 50 of 500 mg/kg mouse (data not shown). UV3, gemcitabine, and the combination were all more effective than the control (p < 0.05).…”
Section: Uv3 Slowed the Growth Of Cd54 1 Human Tumors In Scid Micementioning
confidence: 99%